The influence of framework material on stress distribution in maxillary complete-arch fixed prostheses supported by four dental implants: a three-dimensional finite element analysis. Issue 14 (10th November 2021) - Dayan, Suleyman Cagatay; Geckili, Onur
Abstract: The purpose of the present study was to compare the stress distribution patterns of four materials used for the framework of All-on-4 prostheses. Following framework materials were evaluated: PEKK, PEEK, titanium, and monolithic zirconia. Bilateral 150 N axial and oblique loads were applied in the first molar region and analyzed using FEA. The highest maximum principal stress and minimum principal stress values in cortical bone were found to appear with PEKK and PEEK frameworks around the posterior dental implants upon oblique loading. The fabrication of frameworks from rigid materials in All-on-4 prostheses reduces stress in dental implants and peri-implant bone when the distal implants are tilted 30°.